The Effects of Regulations and Business Cycles on Temporary Contracts, the Organization of Firms and Productivity - Marcela Eslava; John Haltiwanger; Adriana Kugler; Maurice Kugler (Universidad Nacional de La Plata, Centro de Estudios Distributivos, Laborales y Sociales (CEDLAS), 2014)
We assess the impact, on workforce contract composition, employment adjustment dynamics and productivity, of a combination of changes in the Colombian labor legislation which increased firm's ability of using contracts of a temporary nature, and posterior changes that increased the costs associated with longer term contracts. Until 1990, labor regulations in Colombia practically banned the possibility of using fixed-term contracts for horizons of less than one year (see, e.g. Kugler, 2004). The labor market component of a broad package of market reforms adopted at the beginning of the nineties opened the possibility of hiring under fixed term contracts of different types. Some of these contracts not only free employers of potential dismissal costs, but are also subject to reduced, or even zero, non-wage costs. Regulatory changes occurred in the decade that followed further increased incentives to use fixed term contracts.
Keywords: 330